Activation of a Frizzled-2/β-adrenergic receptor chimera promotes Wnt signaling and differentiation of mouse F9 teratocarcinoma cells via Gαo and Gαt - Liu, Xunxian (The National Academy of Sciences, 1999)
The frizzled gene family of putative Wnt receptors encodes proteins that have a seven-transmembrane-spanning motif characteristic of G protein-linked receptors, though no loss-of-function studies have demonstrated a requirement for G proteins for Frizzled signaling. We engineered a Frizzled-2 chimera responsive to β-adrenergic agonist by using the ligand-binding domains of the β(2)-adrenergic receptor. The expectation was that the chimera would be sensitive both to drug-mediated activation and blockade, thereby circumventing the problem of purifying soluble and active Wnt ligand to activate Frizzled. Expression of the chimera in zebrafish embryos demonstrated isoproterenol (ISO)-stimulated, propranolol-sensitive calcium transients, thereby confirming the β-adrenergic nature of Wnt signaling by the chimeric receptor. Because F9 embryonic teratocarcinoma cells form primitive endoderm after stable transfection of Frizzled-2 chimera and stimulation with ISO, they were subject to depletion of G protein subunits. ISO stimulation of endoderm formation of F9 stem cells expressing the chimeric receptor was blocked by pertussis toxin and by oligodeoxynucleotide antisense to Gαo, Gαt2, and Gβ2. Our results demonstrate the requirement of two pertussis toxin-sensitive G proteins, Gαo and Gαt, for signaling by the Frizzled-2 receptor.